Transient field measurements of g-factors for 24Mg AND 26Mg - Eberhardt, J.L.; Horstman, R.E.; Heeman, H.W.; Middelkoop, G. van (Elsevier, 1974)
The g-factors of the first-excited Jπ = 2+ states of 24Mg and 26Mg have been measured with the ion-implantation perturbed angular correlation technique (IMPAC). The precession of the spins of nuclei recoiling into a magnetized iron backing is predominantly caused by the transient magnetic field for these very light and short-lived (τm ≈ 1 ps) nuclei. The transient field, which attains a value of 200 T for the Mg isotopes, is present only during the slowing-down of the recoiling nucleus and results in average precession angles of about 1.5 mrad. The experimental results are treated in the framework of the transient field theory of Lindhard and Winther. This yields g-factors of G = +0.42b ± 0.09 and G = +1.3 ± 0.3 for 24Mg and 26Mg, respectively. The results are compared with theoretical predictions and for 24Mg also with a recent time-differential deorientation experiment.
Keywords: Natuur- en Sterrenkunde; Nuclear reaction